A longitudinal analysis of the relationship between housing insecurity and physical health among midlife and aging adults in the United States - Aarti C. Bhat; David M. Almeida; Andrew Fenelon; Alexis R. Santos-Lozada (Elsevier, 2022)
Rationale: A large body of work demonstrates the impact of housing instability on health by exploring the effects of evictions and homelessness on psychological wellbeing of young adults and children. However, limited research leverages national longitudinal data to examine whether and how experiences of a range of housing insecurity events, rather than just eviction or homelessness, affect physical health among midlife and older adults. Objective: The current study examines (1) prevalence of housing insecurity among midlife and older adults by age and race, (2) linkages between housing insecurity experiences and facets of physical health, and (3) age and race moderations on these effects. Method: This study employs regression models to examine whether experiences of housing insecurity affect self-rated physical health and chronic physical conditions among midlife and older adults (N = 2598) leveraging two waves of the National Study of Midlife in the United States (MIDUS). Results: Models revealed that housing insecurity experiences predicted poorer self-rated physical health and additional chronic conditions, even when controlling for previous physical health. Moderation analyses indicated that housing insecurity has a stronger relationship with chronic conditions among midlife adults as compared to older adults, and among Black adults as compared to white adults. These results suggest that experiences of housing insecurity leave adults vulnerable to compromised physical health, and that housing insecurity experiences may be particularly detrimental to the health of midlife Black adults. Conclusions: This research adds to the extant literature by introducing a comprehensive measure of housing insecurity experiences, and contributes to a life course perspective regarding how housing insecurity can affect physical health. This research has implications for policy that addresses housing insecurity as a public health concern, especially in the aftermath of the 2008 recession and the economic and housing crisis caused by the COVID-19 pandemic.